The kidney : from normal development to congenital diseases - Vize, Peter D.; Woolf, Adrian S.; Bard, Johnathan B. L. (Academic Press, 2003)
Organogenesis of the kidney has been intensely studied for over a century. In recent years advances in molecular techniques have not only made great inroads into exploring the genetic regulation of this complex process but also began to unravel the molecular basis of many forms of congenital kidney disease. This book is a comprehensive study on these findings and the only book available with such in depth coverage of the kidney. Key Features * Hundreds of color figures depicting key events in all aspects of kidney development * Full coverage of the genetic and cellular basis of kidney development * Analysis of the genetic basis of the major congenital kidney diseases.